The role of interleukin-18 and interleukin-18 binding protein in K/BxN serum transfer-induced arthritis - Fauteux-Daniel, Sebastien; Merlo Pich, Laura M.; Girard-Guyonvarc’h, Charlotte; Caruso, Assunta; Rodriguez, Emiliana; Gabay, Cem (Frontiers in Immunology, 2023)
Background: Interleukin-18 is a proinflammatory cytokine, the activity of which is regulated by its natural inhibitor IL-18 binding protein (IL-18BP). Elevated circulating levels of IL-18 have been observed in patients with systemic juvenile idiopathic arthritis (sJIA) and adult-onset Still’s disease (AOSD), two conditions associated with dysregulated innate immune responses. This study examines the expression and function of IL-18 and IL-18BP in K/BxN serum transfer arthritis (STA), a model that is uniquely dependent on innate immune responses. Methods: Naïve and STA wild-type (WT) mice were used to examine the articular levels of IL-18 and IL-18BP mRNA by RT-qPCR. The cellular sources of IL-18BP in the joints were determined by using Il18bp-tdTomato reporter knock-in mice. The incidence and severity of arthritis, including mRNA levels of different cytokines, were compared in IL-18BP or IL-18 knock-out (KO) mice and their WT littermates. Results: IL-18 and IL-18BP mRNA levels were significantly increased in arthritic as compared to normal joints. Synovial neutrophils, macrophages and endothelial cells represented the cellular sources of IL-18BP in arthritic joints, whereas IL-18BP production was limited to endothelial cells in non-inflamed joints. The incidence and severity of arthritis was similar in IL-18BP KO and IL-18 KO compared to their WT littermates. Transcript levels of different inflammatory cytokines were not different in the two KO mouse lines compared to WT mice. Conclusion: Although IL-18 and IL-18BP levels were increased in arthritic joints, our results show that the IL-18/IL-18BP balance is not involved in the regulation of STA.